Good results with cemented total hip arthroplasty in patients between 40 and 50 years of age: 168 hips followed for 2–19 years - de Kam, Daniël C J (Informa Healthcare, 2010)
Background and purpose Total hip arthroplasties in young patients have lower long-term survival rates than in older patients. We evaluated the use of a unique treatment protocol in patients aged between 40 and 50 years. In all cases we used a cemented THA, and for acetabular deficiencies we also used impacted bone grafts together with a cemented cup. Methods In 140 consecutive patients who were between 40 and 50 years of age at index surgery, 168 cemented total hip prostheses were evaluated after a mean follow-up time of 10 (2–19) years. Acetabular deficiencies were reconstructed with wire meshes and impacted bone grafts with a cemented cup (70 hips). During follow-up, 18 patients died (27 hips); in this group 3 hips (3 patients) had been revised. None of the patients were lost to follow-up. In all surviving patients, clinical assessment was performed with hip-score questions and all radiographs were evaluated. Results All clinical questionnaires showed an improved clinical hip score. 29 hips (17%) were revised after a mean of 8 (0.3–18) years. Kaplan-Meier survival analysis showed a survival of 88% (95% CI: 82–94) after 10 years with revision of either component for any reason. Survival with endpoint revision for aseptic loosening of either component was 94% (95% CI: 90–99) after 10 years. Interpretation Cemented implants in young patients have satisfying long-term results. Reconstruction of acetabular deficiencies with impacted bone grafts show promising results.